Revision of the Culicoides (Avaritia) Imicola complex Khamala & Kettle (Diptera: Ceratopogonidae) from the Australasian region - Bellis, Glenn; Dyce, Alan; Gopurenko, David; Yanase, Tohru; Garros, Claire; Labuschagne, Karien; Mitchell, Andrew (Zootaxa, 2014)
The monophyly of the Imicola complex, a natural species complex within subgenus C. subgen. Avaritia Fox of the biting midge genus Culicoides Latreille, is supported using morphological and molecular analyses. A diagnosis for the group along with comparative redescriptions of the male and female of the species represented in Australasia, C. brevitarsis Kieffer and C. nudipalpis Delfinado and a description of C. asiatica Bellis sp. nov., are presented together with keys for their specific determination and molecular support for their status.